Parent reflections of experiences of participating in a randomized controlled trial of a behavioral intervention for infants at risk of autism spectrum disorders. (July 2014) - Freuler, Ashley C; Baranek, Grace T; Tashjian, Christene; Watson, Linda R; Crais, Elizabeth R; Turner-Brown, Lauren M
Background: Despite the mounting evidence of efficacy of early intervention for children with autism spectrum disorders, there is little research that considers the various perceptions and resources with which parents respond to the pressures and opportunities associated with participation in early intervention. Research is particularly lacking surrounding experiences of parents with infants who are at risk of autism spectrum disorders but do not (yet) have a diagnosed condition. Objectives: This qualitative study aimed to explore the experiences of caregivers following their participation in a randomized controlled trial of Adapted Responsive Teaching, a parent–infant relationship-focused intervention for infants at risk of autism spectrum disorders in a community sample. Parents were randomized into either the treatment group, in which they participated in the Adapted Responsive Teaching intervention, or the community services group, in which they were provided with information regarding local early intervention services and were encouraged, but not required to, seek community services as part of their inclusion in the randomized controlled trial. Methods: Semistructured interviews were conducted with families following the completion of the randomized controlled trial. Participants consisted of 13 mothers and 4 fathers. Five dyads were interviewed together for a total of 14 families. Child ages ranged from 39 to 46 months at the time of interview. Analysis was conducted on 14 interviews from 10 families who were randomized into the treatment group and 4 families randomized into the community services group. Analysis was informed by a thematic analysis approach, which involved a systematic process of coding and theme identification both across and within groups. Results: Themes that emerged across groups included Working against all odds, Value of the personal relationship, Getting the ball rolling, and Getting dad on board . One broad theme represented the data within the groups: Win-win (Adapted Responsive Teaching group) and Navigating amidst ambiguity (community services group). Conclusions: This study illuminates the personal experiences and contextual influences affecting families who are participating in the randomized controlled trial through early identification of "risk" status for autism spectrum disorders in their infants. Insights gained from these interviews may serve to refine and enhance intervention models and to enhance early intervention services for families.